Transformer Magnetizing Inrush Currents Using a Directly Coupled Voltage-Source Inverter. (31st October 2013) - Ekström, Rickard; Apelfröjd, Senad; Leijon, Mats
Abstract : The connection of a power transformer to the grid is associated with magnetizing inrush currents that may result in power quality issues as well as faulty relay tripping. In distributed generation, the transformer may instead be premagnetized from the source to avoid this. In this paper, a VSI is directly coupled to a transformer. Three different strategies of premagnetization are implemented into the control system, and the inrush currents are measured for various values of the remanent flux in the core. The results show good reduction in the peak magnetizing inrush currents without using any external circuitry.